Elite sailors: are their hearts all the same? - Garcia-Borbolla Fernandez, R.; Vaz Pardal, C.; Ruiz Verdeja, C.; Gomez-Plana Núnez, F.; Fernandez Chamizo, E.; Garcia-Borbolla Fernandez, M. (Archivos de medicina del deporte, 2008)
During the past decade some studies have been conducted to evaluate the energy demands of sailing. The results indicate that sailing in RS:X, Laser and Finn classes are associated with a high energy demand level. Never theless, as far as is known, no studies have analyzed the heart of elite sailors. The aim of the present study was to analyze ecocardiographic parameters of our group of Spanish elite sailors from different Olympic classes. Methods: 30 elite male sailors from the different Olympic Sailing classes were recruited. An echocardiogram was performed on each sailor as well as a maximal incremental exercise test on a cycloergometer in order to assess maximum oxygen uptake. Gas exchange and respiratory parameters were directly measure breath by breath. The study subjects were separated into two different groups: Group 1 (14 sailors) including RS:X, Finn and Laser class (those with a higher metabolic requirements), and group 2 (16 sailors) from the other classes. Results: Measurement of left ventricle telediastolic diameter in group 1 was 59.2±2 mm, versus 52±2.1 mm in group 2 (p<0.05). Those sailors with a greater ventricle diameter also presented a higher maximum oxygen uptake on the cycloergometer test compared to other classes (59.42±5.4 ml.kg -1 .min -1 vs. 52.68±4.01 ml.kg -1 .min -1 ), similar to that of other dynamic sports like rowing or canoeing. Conclusions: In conclusion, this study shows that the heart of the elite sailors differs according to the class sailed. The sailors of RS:X, Laser and Finn class present greater ventricular diameters and higher oxygen consumption.